Intensitas Pola Asuh Authoritative Anak Usia Dini Yang Memiliki Ibu Tenaga Kerja Wanita Terhadap Hasil Belajar Di Sekolah Di Bajang Mlarak Ponorogo Propinsi Jawa Timur - Lestari, Mukti; Andrian, Dyka (Universitas Merdeka Madiun, 2018)
Parenting patterns is greatly affect the lives of children and the learning outcomes they obtain at school. This research is qualitative descriptive, where data is obtained from observation, in-depth interviews, and documentation. The data analysis is carried out interactively and continuously so that the data is saturated. The activity of data analysis such as data reduction, datadisplay and conclusion drawing. From the results of the research can be known that children who have mothers as TKW still get a good parenting pattern from substitute caregivers or from his/her mothers as TKW with authoritative care such as not restricting children's freedom to play and learn and giving freedom to act as long as they positive thing. Learning outcomes of the children who have mothers TKW in TK Bajang Mlarak Ponorogo is well developed,include of cognitive, affective and psychomotor aspects.